Perceived barriers and facilitators to exercise adherence in osteoarthritis: A thematic synthesis of qualitative studies - Benedetto Giardulli; Davide Marazzi; Alessandro Nespoli; Gaia Leuzzi; Andrea Dell'Isola; Yeliz Prior; Simone Battista (Osteoarthritis and Cartilage Open)
Objective: Exercise is a first-line intervention for osteoarthritis (OA). However, exercise adherence remains low, and existing studies exploring factors influencing adherence have yielded inconclusive results based on quantitative data. This study aims to synthesise qualitative studies focused on the perceived facilitators and barriers affecting exercise adherence in individuals with OA. Design: A thematic synthesis of qualitative studies was conducted. Relevant articles were sourced from MEDLINE, Cochrane Central Register of Controlled Trials, Embase, CINAHL, and PsychInfo until November 2024. Studies focused on adults (≥16 years) with hip or knee OA who had participated in exercise programmes to manage OA. The quality of the studies was assessed using the Critical Appraisal Skills Programme (CASP) tool. Data analysis followed Thematic Synthesis by Thomas & Harden to identify descriptive and analytical themes. The confidence of the evidence was evaluated through the Confidence in Evidence from Reviews of Qualitative Research (CERQual). Results: A total of 21 studies involving 458 participants were included. From seven descriptive themes, three analytical themes were developed: (i) Mind-Body Connection, (ii) Social Support Systems, and (iii) Environmental Enablers. These themes underscore the importance of personal beliefs, experiences, and mindsets, alongside social and environmental factors, in promoting or hindering exercise adherence. Conclusion: This study highlights the multifaceted cognitive, social, and environmental factors influencing exercise adherence in individuals with OA. The findings suggest that a ‘one-size-fits-all’ approach is insufficient for promoting sustained exercise engagement. Future quantitative research should build upon these insights to develop tailored strategies for enhancing exercise adherence in people with OA.